EFFECT OF BASIC AMENITIES ON SOCIO-ECONOMIC DEVELOPMENT OF RURAL AREAS IN BENUE STATE NIGERIA - ONYOWO REBECCA ATUNGWU (International Studies Journal)
The study determined the effect of basic amenities on socioeconomic development of rural areas in Benue State, Nigeria. The study specifically determined the effect of primary healthcare, pipe-borne water, education, and rural electrification on socioeconomic development of rural areas in Benue State, Nigeria. The study adopted a survey research design and data were collected using structured questionnaire. The population of the study consists of 1,023, 000 people in three selected local government areas in Benue State namely, Vandeikya, Buruku and Ogbadibo. A sample size of 400 was determined using Taro Yamane’s formula. The data collected were analysed using inferential statistics (regression analysis). Findings of the study indicated that primary healthcare, pipe-borne water, education, and rural electrification have significant effect on socioeconomic development of rural areas in Benue State, Nigeria. The study concluded that basic amenities have helped in the transformation of rural areas in Benue State. It recommended amongst others that Local government areas in Benue State should always provide healthcare facilities and improve on healthcare services for the rural dwellers. This will help to improve the living conditions of the people in rural areas, Local government councils in Benue State should always ensure that water is made available and accessible to rural dwellers to help alleviate their sufferings. Local government should also ensure the maintenance and repair of pipe-borne water in rural areas, Local government areas in Benue State should assist the state government in the establishment and maintenance of rural education as well as ensure the provision of textbooks and audio-visual materials in primary schools to help the plight of the less privileged and to help improve rural electrification, local government areas in Benue State should always provide support and constant maintenance for steady electrification as it has the highest contribution to socioeconomic development of rural areas in Benue state, Nigeria.